Village Community Participation In Village Development - Komaria Nur Aulia (Socio Legal and Islamic Law, 2022)
Village development efforts are not only carried out by the government, but must be accompanied by participation from village communities. Village community participation will be obtained if the program in village development is in accordance with the needs of the village community. Therefore, there is a need for cooperation between the village government and the village community itself. Researchers want to know more about the factors that cause lack of community participation, what the government can do to increase community participation, and what forms of participation can be done by the community in village development. Researchers use literature study data collection techniques by collecting relevant data from books, scientific articles and journals. The results of the study stated that the factors that influence community participation are internal factors of the community itself, such as age, gender, education level etc. To increase community participation, the village government must have a good role as a dynamicator, catalyst and pioneer in every development movement carried out to obtain full participation from the community so that the goals in village development can be achieved.